2021
DOI: 10.3390/cancers13184676
|View full text |Cite
|
Sign up to set email alerts
|

Naples Prognostic Score Predicts Tumor Regression Grade in Resectable Gastric Cancer Treated with Preoperative Chemotherapy

Abstract: Despite recent progresses, locally advanced gastric cancer remains a daunting challenge to embrace. Perioperative chemotherapy and D2-gastrectomy depict multimodal treatment of gastric cancer in Europe, shows better results than curative surgery alone in terms of downstaging, micrometastases elimination, and improved long-term survival. Unfortunately, preoperative chemotherapy is useless in about 50% of cases of non-responder patients, in which no effect is registered. Tumor regression grade (TRG) is directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…25 Although we have found some differences in the immune and nutritional status of CRC and GC patients. However, previous studies still show that the CRC-NPS can effectively predict the prognosis of GC, 10,[26][27][28][29] this indicates that CRC-NPS has good applicability. However, there may be some differences in the nutritional status of patients in different regions and different populations.…”
Section: Discussionmentioning
confidence: 99%
“…25 Although we have found some differences in the immune and nutritional status of CRC and GC patients. However, previous studies still show that the CRC-NPS can effectively predict the prognosis of GC, 10,[26][27][28][29] this indicates that CRC-NPS has good applicability. However, there may be some differences in the nutritional status of patients in different regions and different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Lieto et al. found that assessment of NPS in gastric cancer patients treating with multimodal treatment may be valuable in modulating immune-nutritional conditions in order to improve patient’s reaction against the tumor [ 50 ]. Therefore, NPS may represent different risk grades, suggesting that patients in different groups have different prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, TRG is a better prognostic factor than the Response Evaluation Criteria in Solid Tumors (RECIST)–the most widely used tumor response classification [ 18 ]. In an Italian retrospective study, authors assessed the relation between immune-nutritional status and TRG among resectable GC patients [ 19 ]. Naples Prognostic Scale (NPS) was implemented to verify patient nutritional condition.…”
Section: Introductionmentioning
confidence: 99%